The relationship between environmental disclosures and financial performance of public listed companies in Malaysia - Ong, Tze San; Tho, Huey Shi; Goh, Han Hwa; Thai, Siew Bee; Teh, Boon Heng (Medwell Journals, 2016)
Nowadays, corporations are facing the challenges of publishing environmental disclosures as the public concerns on the environmental issues have increased. A controversial issue is whether firms with environmental disclosures will result in a better financial performance since, there is an increasing trend for large companies chooses to make environmental disclosures voluntarily. This study aims to examine the relationship between environmental disclosures and financial performance of public listed companies in Malaysia. Content analysis approach was adopted to determine the quantity and quality of the environmental disclosure in the annual reports of 100 companies listed on the Main Board of Bursa Saham Malaysia for the year 2009 until 2013. The results show that only the quality of environmental disclosure has the positive relationship with the company’s Earnings per Share (EPS). This study also indicates that larger companies disseminated more environmental information as well as provided better quality disclosure. Interestingly, the results of this study indicated that less environmentally sensitive industries disclosed more and higher quality of environmental disclosure than environmentally sensitive industries. In conclusion, the environmental disclosures practices in Malaysia is still in an adaptation stage as many Malaysia companies still do not disclose any environmental information in their annual reports. Hence, more effective efforts are needed from regulatory bodies to increase the environmental awareness in Malaysia.